1996
DOI: 10.3109/00952999609001665
|View full text |Cite
|
Sign up to set email alerts
|

The Johnson Intervention and Relapse During Outpatient Treatment

Abstract: The Johnson Intervention is a therapeutic technique in which members of a person's social network confront him or her about the damage that drinking and drug use has caused and the action they will take if he or she does not enter treatment. Previously, we evaluated the effectiveness of the Johnson Intervention at engaging and retaining clients in outpatient alcohol and other drug (AOD) treatment by comparing it to four other methods of referral. Although individuals who undergo a Johnson Intervention are most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 10 publications
0
14
0
1
Order By: Relevance
“…Some evidence has been published suggesting that informal pressures, ranging from encouragements to organized interventions to prompt treatment entry, are associated with higher rates of treatment completion relative to self-referred clients [69,72], as well as a greater likelihood of regular attendance at 12-step meetings and methadone treatment [74]. Further study has linked social network pressures to higher rates of abstinence relative to problem drinkers who are not confronted by their friends and family [70], but lower rates of abstinence relative to others in treatment [75]. The methodological quality of these studies is variable, however.…”
Section: Reviewmentioning
confidence: 99%
“…Some evidence has been published suggesting that informal pressures, ranging from encouragements to organized interventions to prompt treatment entry, are associated with higher rates of treatment completion relative to self-referred clients [69,72], as well as a greater likelihood of regular attendance at 12-step meetings and methadone treatment [74]. Further study has linked social network pressures to higher rates of abstinence relative to problem drinkers who are not confronted by their friends and family [70], but lower rates of abstinence relative to others in treatment [75]. The methodological quality of these studies is variable, however.…”
Section: Reviewmentioning
confidence: 99%
“…Also, one study (Loneck, Garrett, & Banks, 1996b) reported that clients who had entered treatment as the result of a confrontation were more likely to relapse than those who entered via other methods of referral. The second strategy has been used in several trials as a standard treatment comparison group using Al-Anon/Nar-Anon or Al-Anon/Nar-Anon Facilitation (ANF), which involves about 10–12 individually-delivered sessions that provide an introduction to Al-Anon/Nar-Anon concepts and active and consistent encouragement to engage in these widely available support groups.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Loneck et al (1996) found that IWA's that had undergone a Johnson Intervention were more likely to relapse than any other referral group of IWA's, including those that had been given ultimatums by a professional body such as a court or employer.…”
Section: Introductionmentioning
confidence: 99%
“…Models such as Community Reinforcement and Family Training (CRAFT) and the Pressure to Change Approach focus on instructing family members on how to best encourage IWA's to attend treatment by teaching family members behavioral procedures to interact with the IWA (Barber and Crisp, 1995;Copello et al, 2005;Meyers et al, 2005). Other techniques, such as The Johnson Intervention, have the family focus directly on the damage the addiction has caused and the ultimatums they will enact if treatment is not sought (Loneck et al, 1996). The Johnson Intervention is the intervention most closely associated with the television series Intervention and up to 80% of IWA's who undergo a Johnson Intervention enter treatment (Loneck et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation